Green Construction: Innovations, Energy Efficiency, and Prospects for Ukraine - Rutkovska, Iryna; Salabai, Roman; Salabai, Iryna (Academic journal Industrial Machine Building Civil Engineering, 2025)
This article explores the concept of green construction as a pioneering approach in contemporary construction, aiming to minimize environmental impact and enhance energy efficiency. Modern approaches to resource use, the implementation of energy-saving technologies, and ecological materials are analyzed. International experience and certification systems, such as LEED, BREEAM, DGNB, and WELL, are reviewed with emphasis on practical application. Special attention is paid to the prospects for green technologies in Ukraine during post-war reconstruction, the formation of sustainable urban ecosystems, and integration into the European space [2–8].